Product ecolabelling, competition and the environment - Alain Nadai; Benoit Morel (Fondazione Eni Enrico Mattei (FEEM), 2000)
The paper explores the impact of a third-party product ecolabel (i.e. green label) on competition and the environment, and the firms' strategies during the negotiation of the minimum environmental requirements underlying a product's eligibility for the ecolabel. The introduction includes some empirical observation about the development of the European ecolabel. The second part presents the model. We assume Cournot competition in a homogenous industry made up of multi-product firms each selling the whole range of product-variants, from green to brown. Green consumers "trust" the ecolabel. We derive demand, supply, prices and profits at the equilibrium before and after ecolabel. We first assume that firms do not innovate on their products. We then introduce environmental innovation into the model. The third part analyses the impact of the ecolabel on competition (firms' profits) and the environment (green innovation and market shares). The conclusion contrasts the results with the ones obtained in the case of a heterogeneous industry - i.e., an industry made up of mono-product firms each selling a product having an environmental profile different than that of the other firms' products- and draws policy considerations. The paper expands the literature on product ecolabelling by considering imperfect competition, giving thus the possibility for the firms to undertake green innovations affecting non marginal costs, and by taking into account the type of industry concerned by the ecolabel. We find that firms in a homogenous industry are better off with an ecolabel than without and might even be willing to adopt environmentally effective criteria if the green demand is important and innovation costs are low. This contrasts with results obtained in a previous paper for a heterogeneous industry, in which part of the firms will always lose from the implementation of an environmentally effective ecolabel and oppose its development. Cross-industry comparison suggests that regulators should start developing ecolabelling programs with homogenous industry in which innovation costs are likely to be negligible as compared to the costs of production.
Keywords: Q28; D43; 330; Quality; ecolabel; voluntary environmental regulation; Umweltzeichen; Selbstverpflichtung; Wettbewerb; Marktanteil; Innovation; Theorie